PRESEPSI ORANG ASLI TERHADAP PENDIDIKAN (Study Kasus Terhadap Orang Asli yang ada di Desa sungai Upih Kecamatan Kuala Kampar Kabupaten Pelalawan) - Kurniadi "; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Kurniadi, the Perception of Indigenous People (orang asli) to Education.Thesis, Sociology Department, Social Science and Politics Faculty, University ofRiau. The advisor Drs. Jonyanis, Msi. Orang Asli (indigenous people) are societyof suku akit that live with manage the resource of poor. They have difficulties tofree of poor because they have some limited in quality of human resource, accessand technology, market and capital. Society is main characters in development. Tofind out the potency of human, so that we need education. The implementation ofthe education is our responsibility between family, school and society. Educationof children is influenced by some factors they are condition of social economyand the environment of someone live are not same, the mores, habit,psychologies, bureaucracy, the sense and behavior to school, etc. Based onbackground above and basic of mind, the formulation of the problem is: how theperception of indigenous people (orang asli) to children education in Desa SungaiUpih district of Kuala Kampar sub province of Pelalawan, and what the factorsthat influence the perception orang asli to children education in Desa SungaiUpih district of Kuala Kampar sub province of Pelalawan. The purpose of thisresearch are to know the perception of orang asli to education in Desa SungaiUpih district of Kuala Kampar sub province of Pelalawan, and to know thefacctors that influence the perception of orang asli to children education in DesaSungai Upih. This research is qualitative approach and kind of descriptive.Collected the data have done with use observation method, interview, anddocumentation. And then, the data that collected are words that analyze withanalysis descriptive qualitative technique. From the result of discussion andresearch the writer can conclude: how the perception of indigenous people (orangasli) to children education in Desa Sungai Upih district of Kuala Kampar subprovince of Pelalawan is important but only limited to interpret so that thechildren can read and write. While, the factors that influence the perception orangasli to children education in Desa Sungai Upih are the education of parent is low,prosperity, the mores, the expense of school is high, the environment of schooland school distance.Keywords: Indigenous People (orang asli), the Perception and Education.